A new species of the Pholcus phungiformes species group (Araneae, Pholcidae) from Liaoning, China, with identification keys to four closely related species - Ludan Zhang; Bing Wang; Qiaoqiao He; Zhiyuan Yao (ZooKeys, 2024)
A new species of pholcid spiders, Pholcus fengmeii Zhang, He & Yao, sp. nov. (♂♀), is described from Liaoning Province, China. The new species belongs to the speciose phungiformes species group. Taxonomic keys to four closely related species are provided.